Effects of tidal states and time of day on the abundance and behavior of shorebirds utilizing tropical intertidal environment - Ramli, R.; Norazlimi, N. A. (ResearchGate, 2016)
A study was conducted in the mudflats area of Jeram and Remis Beaches, Selangor, Peninsular Malaysia from August 2013 until July 2014 to determine the effect of tidal states and time of the day on shorebird’s abundance and behavior. Direct observation techniques (with the aid of binoculars and a video recording) were used in this study. Twenty three species of shorebirds (Density = 413.3 ind iv/ha) were recorded in both study areas. Mann-Whitney test showed a significant difference in shorebird abundance between high tide and low tide (W = 78.0, p < 0.005) and also between behavior of shorebirds with respect to the tidal state; feeding behavior (W = 222.0, p < 0.0001), preening behavior (W =204.5, p = 0.0017) and mobility behavior (W = 222.0, p < 0.0001). Friedman’s Two-Way ANOVA by Ranks proofs the significant difference occurred in shorebird’s distribution between ebbing, low tide peak, and rising tides (S = 17.17, p < 0.0001). χ² tests were tested for all behaviors engaged by shorebirds during low tide period and the results showed a significant difference between the behaviors (χ² = 1831.9, p < 0.0001). ANOVA analysis showed no significance difference in abundance of shorebirds between interval period (S = 487.0; p = 0.554). However, Friedman’s Two-Way ANOVA by rank test shows the significant difference in abundance of shorebirds in high tide (S = 8.788, p = 0.03) between interval period. On the contrary, the analysis of Friedman’s Two-Way ANOVA by ranks highlighted no significance difference in abundance of shorebirds in low tide (S = 4.526; p = 0.21) between interval time. Therefore, this study showed that the tide does influence the shorebird’s abundance and behavior whereas time of the day does not have significant effect on both shorebird’s abundance and behavior.